2013
DOI: 10.1111/apa.12433
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breastfeeding for 4 versus 6 months and growth in early childhood

Abstract: Exclusive breastfeeding for the first 4 or 6 months of life does not seem to affect the risk of being overweight or the prevalence of those who were overweight in early childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 26 publications
2
37
0
1
Order By: Relevance
“…The observed similarity of BMI trajectories among partial and exclusive breastfed Swedish children in our study may be explained by the quite small difference in duration of exclusive breastfeeding in the two groups and is compatible with literature . In addition, it is important to highlight that our findings do not contradict current recommendation for exclusive breastfeeding.…”
Section: Discussionsupporting
confidence: 90%
“…The observed similarity of BMI trajectories among partial and exclusive breastfed Swedish children in our study may be explained by the quite small difference in duration of exclusive breastfeeding in the two groups and is compatible with literature . In addition, it is important to highlight that our findings do not contradict current recommendation for exclusive breastfeeding.…”
Section: Discussionsupporting
confidence: 90%
“…Worldwide substantial adverse health and nutritional outcomes are attributed to lack of EBF [ 23 , 24 ]. Results of this study suggest a protective effect of EBF against diarrhea, ARI and fever.…”
Section: Discussionmentioning
confidence: 99%
“…Results from a randomized controlled trial performed in Iceland, showed no significant differences in energy intake [15], growth [14], or risk of being overweight [13] between those exclusively breastfed for 4 vs . 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that formula fed children grow more rapidly than children who are exclusively breastfed [11,12] and are at greater risk of childhood overweight or obesity [6] but less is known about the long-term effects of early solid food introduction in early infancy. In a recent randomized controlled trial, introduction of complementary feeding at 4 months of age did not increase weight gain in infancy and did not appear to affect the risk of overweight or obesity at 18 months or 29–38 months of age compared to infants exclusively breastfed for 6 months [13,14,15]. The aim in this current analysis was to assess the associations between infant feeding practice in early infancy and body mass index (BMI) at 6 years of age.…”
Section: Introductionmentioning
confidence: 99%